Premenstrual syndrome, coping mechanisms and associated factors among Wolkite university female regular students, Ethiopia, 2021 - Natnael Eshetu; Haimanot Abebe; Elishaday Fikadu; Serkalem Getaye; Seid Jemal; Shegaw Geze; Yibeltal Mesfin; Seboka Abebe; Daniel Tsega; Bitew Tefera; Wubishet Tesfaye (BMC, 2022)
Abstract Background Premenstrual syndrome (PMS) is used to describe physical, cognitive, affective, and behavioral symptoms that affect young and middle-aged women occurring cyclically during the luteal phase of the menstrual cycle. Despite the considerable prevalence and impact of PMS on individuals, their families and communities that interferes with the development of nations, many professionals are still unaware of it and little attention has been given in developing countries like Ethiopia, especially for university students. Therefore, this study was aimed for assessing the magnitude of premenstrual syndrome, associated factors and coping mechanisms among Wolkite university female regular students, 2021. Methods Institutional-based cross sectional study was conducted among Wolkite University regular female students from June 15/10/2021 to 30/10/2021 by using simple random and multistage with systematic random sampling technique to select the study participants (n = 591). Data were collected using a self-administered, pre-tested, semi-structured questionnaire. Premenstrual syndrome scales comprised of 40 questions with three sub-scales were used to determine Premenstrual syndrome. Data were cleaned, coded and entered into Epi-data version-3.1, and analyzed using SPSS software version 25. Descriptive statistics were computed for independent variables as well as for coping mechanisms and presented in narration, tables and graphs. Analytic analysis schemes including bi-variable and multivariable logistic regression were computed to identify factors associated with premenstrual syndrome and those variables with a P value of < 0.05 in multivariable analysis were declared as statistically significant. Result From the total of 631 study subjects, only 591 had completed the questionnaire, giving a response rate of 93.7%. From 591 study participants, 224 (37.9%) [95% CI: (34, 40.9)] of them had premenstrual syndrome. Abdominal cramp (78.8%), depression (73.3%) and fatigue (72.9%) were frequent premenstrual symptoms experienced by students. Having family history of PMS [AOR: 4.05; 95% CI: (2.49, 6.58)], no history of sexual intercourse [AOR: 2; 95% CI: (1.12, 3.47)], severe menstrual pain intensity [AOR: 3.09; 95% CI: (1.58, 6.05)], irregular menstrual cycle [AOR: 2.26; 95% CI: (1.41, 3.62)], early age of menarche (< 13 years) [AOR: 2.64; 95% CI: (1.34, 5.19)], long duration of menses (≥ 7 days) [AOR: 3.56; 95% CI: (1.53, 8.37)] and using many pads (> 8) during menstruation [AOR: 4.44; 95% CI: (2.16, 9.12)] were factors significantly associated with premenstrual syndrome. 93.4% of students apply at least one coping mechanism for premenstrual symptoms, of which; taking rest (67.6%) and sleeping (60.7%) were common strategies. Conclusion In this study, premenstrual syndrome was found to be a problem of many students. Abdominal cramp, depressed feeling and fatigue were the predominant premenstrual symptoms experienced by students. Taking rest and sleeping were mostly applied by students as a coping mechanism. Family history of PMS, no history of sexual intercourse, intense menstrual pain, use of many pads during menstruation, irregular menstrual cycle, early menarche, and long duration of menses were found to be predictors of premenstrual syndrome. PMS needs great attention as part of the health care service in Ethiopia by involving all stockholders, including policy makers and health care professionals, to reduce its impact on the academic performance of university students.